Sosialisasi Penerapan Sistem Budidaya Aquaponik dengan Budikdamber (Budidaya Ikan dalam Ember) pada Lahan Terbatas di Desa Banjaragung, Kabupaten Jombang - Marsha Amanda Fahrasyahda; Mu’tasim Billah; Dona Wahyuning Laily (Jurnal Informasi Pengabdian Masyarakat, 2023)
The growth of society in Indonesia is still quite uneven. This has resulted in a very diverse community economic situation, so that each region is required to be able to empower itself from a social and economic perspective. One of them is in agriculture which is very commonly carried out by rural communities. However, not all rural communities have large areas of land to be used as agricultural facilities, such as the people of Banjaragung Village, Jombang Regency. Therefore, efforts are needed to be able to utilize limited land, one of which is by cultivating fish in buckets (budikdamber). Group 02 KKN-T MBKM UPN "Veteran" East Java carried out a civics socialization activity targeting PKK Banjaragung women to provide information regarding community awareness raising activities in utilizing limited land. The approach to carrying out this task is through 1) literature study, 2) socialization, and 3) making budikdamber. The result of this activity is to be able to provide new knowledge and knowledge to members of the Banjaragung Village PKK. This outreach was positively welcomed by all participants.